SYNTHESIS, CHARACTERIZATION OF NEW HYBRID MATERIAL BASED ON POLYPYRROLE-TETRATHIAFULVALENE AND ZINC OXIDE - Tiaouinine, Siham; Kaboub, Lakhemici; Hamza, Djamel-Eddine; Azizi, Amor; Gouasmia, AK. (University of Eloued جامعة الوادي, 2018)
Her we report a preliminary study of material witch an organic material is combined with an inorganic material to yield a solar cell. ZnO was deposited electrochemically onto glass/ITO form aqueous solutions containing KNO3 and Zn (NO3)2. New molecule TTF donor (TTF: tetrathiafulvalene) containing pyrrole has been synthesized and its electron-donating ability determined by cyclic voltammetry. Then, Polypyrrole -TTF films have been grown on ZnO substrates from an acetonitrile solution of TBAPF6 - by the electropolymerisation technique. The chemical composition of the ZnO/Polypyroole-TTF films was determined by UV and IR spectroscopy. The morphology of the prepared film layers were detrmined using the AFM technique. Lastly, the band gap of the heterojunction, between the HOMO of the donor material Polypyrrole-TTF and the LUMO of the of the acceptor layer (ZnO) were estimated by UV-vis absorption spectra. This study shows a decrease in the gap energy value from 3.88 to 3.55 eV proved the interaction between the hybridbilayer
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Polypyrrole -TTF films, hybrid material, photovolyaique